2014
DOI: 10.1002/dneu.22190
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Agrin and Wnt signaling pathways in development of vertebrate neuromuscular junction

Abstract: Neuromuscular junction (NMJ) is a cholinergic synapse where motor neurons elicit muscle contraction. Agrin and its coreceptors LRP4 and MuSK are critical for vertebrate NMJ formation. This paper reviews recent evidence for Wnts and Wnt signaling molecules in NMJ formation including a possible retrograde mechanism by muscle β-catenin. We also present data that Wnt3a, 7a, 8a and 10b could inhibit agrin-mediated AChR clustering. Together with the stimulating effect of Wnt9a, 9b, 10b, 11 and 16 on AChR clustering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 81 publications
1
59
1
Order By: Relevance
“…As such, the first Ig-like domain plays an essential role in stimulation of MuSK by Agrin, which is crucial for synapse formation. The presence of a Fz-like domain in MuSK led to speculation that Wnts may bind to MuSK and regulate MuSK activity at one or more stages during synapse formation (Masiakowski and Yancopoulos 1998; Xu and Nusse 1998; Koles and Budnik 2012;Barik et al 2014). Consistent with this idea, the MuSK Fz-like domain as well as Wnt4 and Wnt11r play important roles in muscle prepatterning in zebrafish (Jing et al 2009).…”
Section: Discussionmentioning
confidence: 49%
“…As such, the first Ig-like domain plays an essential role in stimulation of MuSK by Agrin, which is crucial for synapse formation. The presence of a Fz-like domain in MuSK led to speculation that Wnts may bind to MuSK and regulate MuSK activity at one or more stages during synapse formation (Masiakowski and Yancopoulos 1998; Xu and Nusse 1998; Koles and Budnik 2012;Barik et al 2014). Consistent with this idea, the MuSK Fz-like domain as well as Wnt4 and Wnt11r play important roles in muscle prepatterning in zebrafish (Jing et al 2009).…”
Section: Discussionmentioning
confidence: 49%
“…Their function during the formation of the NMJ has been best described in invertebrates (Drosophila melanogaster and Caenorhabditis elegans), and involvement of Wnt signaling at the vertebrate NMJ has also been revealed (reviewed in Refs. 24,232). Wnts in mammals signal through 11 different Frizzled (Fzd) receptors to regulate, via at least five different transduction pathways involving Dishevelled (Dvl), various cellular processes (FIGURE 3C).…”
Section: Wntsmentioning
confidence: 99%
“…However, this does not preclude the compensatory secretion of Wnts by other cells. Moreover, several groups have shown that, in addition to Wnt4 and Wnt11, other Wnt proteins are able to stimulate AChR clustering in the absence (Wnt9a, 9b, 10b and 16) or presence (Wnt3) of exogenous neuronal agrin in vitro (Barik et al, 2014;Henriquez et al, 2008), suggesting that NMJ formation is likely to require the coordinated function of multiple pro-synaptogenic Wnts and that Wnt functional redundancy and/or compensatory mechanisms that are dependent on the genetic background might also in part explain why single or double Wnt deletion in mice can induce distinct NMJ phenotypes. GOF, gain of function; Sfrp4 and Dkk1 refer to direct injections of protein.…”
Section: Coordinated Roles Of Wnt4 and Wnt11 In Achr Clusteringmentioning
confidence: 99%
“…Among the 19 Wnts currently identified in mammals, Wnt2, 3a, 4, 6, 7b, 9a and 11 directly interact with MuSK but only Wnt4, 9a and 11 enhance AChR clustering in muscle cells (Barik et al, 2014;Strochlic et al, 2012;Zhang et al, 2012). In zebrafish, both Wnt4a and Wnt11r initiate muscle prepatterning, probably by stimulating PCP-dependent MuSK endocytosis in muscle cells (Gordon et al, 2012;Jing et al, 2009).…”
Section: Introductionmentioning
confidence: 99%